Sequence Analysis of New Isolated O-methyltransferase Transcript (VMPOMT) from Vanda Mimi Palmer - Barudin, Mohd Aiman; Mohd Hairul, Ab. Rahim; Tan, Suat Hian (Scholars Academic and Scientific Publisher, 2015)
Vanda Mimi Palmer is an orchid hybrid between Vanda Tan Chay Yan and Vanda tessellata. This orchid has won several international awards for its fragrance emission characteristic. To date, scientific studies on enzymes as well as their related genes and transcripts that are involved in floral scent production and biosynthesis are barely covered in fragrant orchids especially in vandaceous orchids. The aims of this study were to isolate full open reading frame (ORF) of O-methyltransferase transcript from Vanda Mimi Palmer (VMPOMT) and followed by sequence characterisation using bioinformatics tools. The size of successfully isolated full-length transcript of VMPOMT (Genbank accession no: KF278721) is 1,289bp, encoding for a polypeptide of 368 amino acid residues consisting of 1,104bp open reading frame (ORF) flanked by 2bp of 5'-untranslated region (UTR) and 182bp of 3'-UTR including a poly-A tail. Sequence analyses using bioinformatics tools have shown that VMPOMT has a conserved motif for O-methyltransferase group as found in OMT sequences from other plants that might be involved in methylation reactions in fragrance compounds biosynthesis in this orchid. Besides that, VMPOMT is predicted to be localised in cytoplasm instead of plastid due to the absence of chloroplast transit peptide in the sequence. Thus, sequence analyses on VMPOMT using several bioinformatics tools might contribute to the understanding of fragrance biosynthetic pathways in Vanda Mimi Palmer as well as in other fragrant orchids